Manajemen Pemasaran Lembaga Pendidikan Islam (Pesantren Modern Darul Ilmi Indonesia) - Jazmi Zulhilmi Putra (Jurnal Syntax Admiration, 2024)
This research aims to determine the marketing management of Islamic educational institutions at the Darul 'Ilmi Indonesia Islamic Boarding School. This research uses qualitative research methods. This research was carried out at an Islamic boarding school, namely the Darul Ilmi Indonesia Modern Islamic Boarding School, which is located on Jl. Raya Puncak Gadog, Pandan Sari Village, West Java, RT.01/RW.03, Ciawi, Kab. Bogor, West Java 16720. Primary data sources were obtained through interview activities with resource persons from the leadership of the Darul Ilmi Indonesia Modern Islamic Boarding School, teaching and education staff, santri guardians, and santri. Data analysis uses the Miles and Hubberman model by reducing, verifying and drawing conclusions. From the research results, it can be concluded that the competitive advantage of modern Islamic boarding school or Islamic boarding school programs can be presented by prioritizing the quality of the educational programs offered. The quality of an educational program is of course reflected through the input, output, process and educational outcomes achieved.